Diseño ágil en la cadena de suministros del sector de bebidas gaseosas (2019)
Nowadays, supply chains tend to be affected due to disturbances created by external factors such as economy, technology, and new government policies. Thus, it’s indispensable that companies can react effectively to accomplish the market’s expectations. This paper established a design that implements solutions through a continual improvement process under the Scrum methodology, adapted to the supply chain of the soft drinks industry as a minimum viable product. The proposed design was evaluated by the applications of serious game dynamics, in which role interactions in the processes of manufacture, sourcing, negotiation, and distribution determined its scopes. Furthermore, the design relies on key process indicators and an income statement that identified the best practices that enhance the obtained results. Based on this, the design created can be implemented in different industries and can help the identification of finding the best solutions for them.